Boosting Critical Thinking Skills: Applying the Dilemma Stories Approach with the 5E Learning Cycle in Buffer Subject Education - Anisa Ayu Solikah; Sulistyo Saputro; Sri Mulyani; Lina Mahardiani; Endang Susilowati; Nanik Dwi Nurhayati; Budi Hastuti; Wirawan Ciptonugroho (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the impact of the Dilemmas approach, rooted in transformative learning, on enhancing critical thinking skills in buffer chemistry subjects among high school students. Employing a mixed-methods design and purposive sampling, the research involved 34 eleventh-grade students from SMAN 1 Surakarta. The implementation of dilemma stories integrated with a 5E learning cycle was scrutinized using various data collection methods, including observations, student reflective journals, pretest-posttest assessments, the Constructivist Chemistry Values Learning Environment Survey (CCVLES), and interviews. Observations assessed the application of the dilemma stories and the 5E learning cycle. Pretest-posttest evaluations measured changes in students' critical thinking abilities, while reflective journals and CCVLES questionnaires captured students' perceptions of their critical thinking skills and their learning experiences. Interviews were conducted to validate the findings from the tests, journals, and questionnaires. Data analysis involved reduction, display, and conclusion-drawing techniques. The findings suggest that the Dilemmas approach significantly fosters students' ability to think critically and apply chemical concepts practically. This was evidenced by students' analyses of dilemma stories and responses in interviews, CCVLES questionnaires, and reflective journals, indicating a deeper engagement with and understanding of the subject matter through this innovative learning strategy.